Avaliação da qualidade de serviços em uma instituição privada de ensino superior do Alto Paranaíba/MG - (:unkn) unknown (Universidade Federal de Goiás, 2016)
Education is the master spring of the development of any nation, and, therefore, we must fight for the Brazilian education is the main goal of public policy. So understanding how is the quality in educational service provision becomes critical. This research aims to evaluate the quality of educational services provided in a private institution of higher education, in the view of students, teachers and administrators through the Servqual. The methodological approach used for this work, it is a descriptive and cross-sectional cohort. As for the approach is a quantitative research and, on the procedures of the research, we used the survey. The target population of this study consists of 345 people, comprising students, teachers and managers of management courses, agronomy and pedagogy. The sample was removed with a 90% confidence level, totaling 161 people. It was used as date collection instrument structured questionnaire, the Servqual, for measuring service quality, adapted to the educational, specific services for students, teachers, and managers of a higher education institution. First, the questionnaire was applied to the expectation, and then on the perception, in order to compare them, and get insight into the quality of services. The collected data were entered and tabulated in Microsoft Excel 2010 program, as well as through IBM SPSS statistical software 20. The reliability analysis was performed using the coefficient of the sample Cronbach's Alpha, and values of alpha coefficient was higher than 0.8 in almost all dimensions, showing the internal consistency of the scale. The results showed that for the three groups of actors, the quality of services obtained unsatisfactory results in all five dimensions: tangibles, reliability, security, empathy and promptness. The tangibility proved to be the size that demands greater attention from the research institution, specifically in relation to computing resources, other website, academic portal and the equipment used. Other critical points were detected in relation to the performance evaluation of staff and the provision of continuous training, and for the understanding of the peculiarities of each student. It is understood, through this research, that the role of an HEI, based on education as a social practice, in addition to teaching responsibilities of training and development of knowledge of all individuals involved, there are other responsibilities in question. The quality services demonstrates the concern of the institution and its students, faculty, staff and society as a whole. That means, provide quality services means acting on behalf of customers and not necessarily in search of profits. It is concluded that the use of Servqual to measure the quality of educational services, such as reliability measured by alpha obtained a high and satisfactory results can be disseminated and widely applied in other higher education institutions in order to assess quality data of services.
Evaluation of quality of service in a private institution of higher education in the Alto Paranaiba / MG
Keywords: Expectativa; Percepção; Serviços educacionais; Ensino superior; Expectancy; Perception; Educational services; Higher education; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO